Symbolic Domination : Study of the Interaction of Noble Power in the Election of Village Heads - Jannah, Andi Ifadtul; Mustari, Nuryanti; Taufik, Ahmad (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, 2024)
This study discusses Symbolic Domination (a study of the interaction of aristocratic power in village head elections in Bonto Tappalang Village, Bantaeng Regency). The aim to be achieved in this study is to find out how symbolic domination is in the interaction of aristocratic power in village head elections in Bonto Tappalang Village, Bantaeng Regency and how are the supporting and inhibiting factors of symbolic domination in the interaction of noble power in village heads. Election in Bonto Tappalang Village, Bantaeng Regency. The research method used in this study is a qualitative method. Sources of data used in this study were primary data and secondary data, the number of informants in this study were 7 people. Data collection techniques in this study were interviews and documentation. The research method used in this study is a qualitative method. Sources of data used in this study were primary data and secondary data, the number of informants in this study were 8 people. Data collection techniques in this study were interviews and documentation. The results of the discussion in this study which dominated the nomination of village heads can be achieved using 3 theories, namely Habitus, Modality, and Field or Arena. The Habitus results show that the activities carried out by the village head candidate are to behave well towards the community and must follow the traits of the noble predecessors in order to gain support from the community leadership. Furthermore, the modality results show that in order to win the contestation in the village head election, capital is needed for the elected village head candidates, namely economic capital, social capital and symbolic capital, the more capital combined, the greater the opportunity for profit . Public trusts. Then the results from the field or arena show that the elected village head candidate must have the space or place to rule in the election.